Efficiency enhancement from [60]fulleropyrrolidine-based polymer solar cells through N-substitution manipulation. (October 2015) - Liang, Yulan; Hao, Yajuan; Liu, Xiaodong; Feng, Lai; Chen, Muzi; Tang, Qiangqiang; Chen, Ning; Tang, Mingliu; Sun, Bingbing; Zhou, Yi; Song, Bo
Abstract: A series of fulleropyrrolidine derivatives (FP x, x  = 1–8) with alternating N-phenyl or N-methyl group were prepared as acceptors for polymer solar cells (PSCs) with the purpose of investigating the effect of N-substitutions on the photovoltaic properties of fullerene materials. More importantly, the morphology studies by means of atomic force microscopy (AFM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and space charge limited current (SCLC) measurements revealed that FP1 with N-phenyl group possessed not only appropriate miscibility with P3HT but also high electron mobility, which may account for its optimal photovoltaic properties.